A High-Frequency assessment of the ECB Securities Markets Programme. Issue 1 (15th December 2016) - Ghysels, Eric; Idier, Julien; Manganelli, Simone; Vergote, Olivier
Abstract: Policy impact studies often suffer from endogeneity problems. Consider the case of the European Central Bank (ECB) Securities Markets Programme: If Eurosystem interventions were triggered by sudden and strong price deteriorations, looking at daily price changes may bias downward the correlation between yields and the amounts of bonds purchased. Simple regressions of daily changes in yields on quantities often give insignificant or even positive coefficients and therefore suggest that Securities Markets Programme (SMP) interventions have been ineffective, or worse counterproductive. We use high-frequency data on purchases of the ECB Securities Markets Programme and sovereign bond quotes to address the simultaneity and endogeneity issues. We propose a Vector AutoRegressive (VAR) framework estimated at several frequencies to better measure the SMP impact and its persistence. Our results show that SMP interventions have been effective in reducing yields of government bonds for the countries under the program. (JEL: E52, E44, G12, C58)